POSSESSIVE CONSTRUCTION OF DAWAN LANGUAGE IN EAST BAUMATA VILLAGE, TAEBENU DISTRICT, KUPANG REGENCY - Jeladu Kosmas; Labu Djuli; I Nyoman Reteg (Postgraduate School, Universitas Nusa Cendana, 2021)
This research aims at figuring out possessive construction of Dawan Language in East Baumata Village, Taebenu Sub-disctrict, Kupang Regency. The result of the study shows that posesor in Dawan in East Baumata Village, consists of animate beings (animate) and inanimate beings (inanimate). Inanimate possessors consist of humans and animals, while inanimate beings consist of plants and inanimate objects, such as stones. Semantically, possessive constructions in this language are found in three possessive grammatical relationships (NP-internal relations), namely: meaning ownership(ownership relationship),such as Na David in bidael where bo'nim 'Ox Mr. David fifty-tail', meaning relations section(whole- part relationship),such as Bi Merry muti bilsin missin 'teethwhite clean Meri', and the relation of meaning familial / kinship(kinship relationship), such as Bi Susan bi mokof anmate ton nuan duen 'Grandfather Susan died two years ago'. The possessive construction of the Dawan language in East Maumata Village, Taebenu District, Kupang Regency in general, the owner (possessor) always appears in the left position or precedes the possessor (possessed), both of which appear with the possessive marker mui 'belonging' and constructions that appear without the marking.